Do depression and its associated factors differ in women daytime and shift workers?: an analysis of the Korea National Health and Nutrition Examination Survey 2018 - Hyun Ju Chae; Mijong Kim (Korean Society of Women Health Nursing, 2021)
Purpose This study examined health behaviors, use of health services, and depression among women who perform daytime and shift work in Korea, as well as factors related to depression. Methods We conducted a secondary analysis using data from the 2018 data of the 7th Korea National Health and Nutrition Examination Survey. Data on women, 1,493 regular daytime workers and 322 shift workers, were analyzed. Results Women shift workers were younger (χ2=43.97, p<.001), had a lower education level (χ2=45.56, p<.001), and lower personal income (χ2=16.85, p=.030) than their daytime counterparts. A higher proportion of shift workers were unmarried (χ2=37.47, p<.001) and they typically worked fewer than 40 hours per week (χ2=69.94, p<.001). The depression score of shift workers was higher than that of daytime workers (t=2.85, p=.005). A higher proportion of shift workers also drank alcohol (χ2=6.49, p=.032) and smoked (χ2=30.79, p<.001). Over 8% of shift workers typically slept fewer than 5 hours per night (χ2=14.17, p=.024). It was confirmed that depression in women shift workers was affected by age, personal income, marital status, health status, and smoking status, in addition to cancer screening participation, unmet medical care needs, and unmet dental care needs. Conclusion More attention should be given to the health needs of women working shifts. Health promotion programs specific for women shift workers are needed to improve their physical and mental health, encourage use of medical care services, and improve public health policies and systems.